Properties of ITO on plastics and glass by Nd:YAG laser deposition at 355 and 532nm - YONG, T; TOU, T; YANG, R; TEO, B; YOW, H (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
Indium tin oxide (ITO) was deposited on polycarbonate (PC), polyethylene terephthalate (PET) and glass substrates at room temperature and in a low-pressure oxygen environment by a pulsed Nd:YAG laser at 355 and 532 nm. The ITO film resistivity varied with the oxygen pressure, which achieved the lowest value of 1.5 x 10(-3) Omega cm from the four-point probe measurements. The highest optical transmittance which depended on the target-to-substrate distance, was determined from UV-vis-NIR spectrophotometer. The highest optical transmission was 94% at 5 cm. The carrier concentration, of the order of 10(19) cm(-3) was determined from the Hall-effect measurements. Those films deposited at 355 nm of laser wavelength did show some better properties as compared to 532 nm. Attempts were made to use these ITO-coated plastic substrates for the fabrication of a organic light-emitting device that was based on single-layer, molecularly doped (poly(N-vinyl carbazole)) (PVK) with a mixture of tris(8-hydroxyquinoline) aluminum (III) (Alq(3)) and N,N'-bis (3-methylphenyl)-N,N'-bis-(phenyl)-benzidine (TPD) of 1:1 ratio. (C) 2008 Elsevier Ltd. All rights reserved.